Characteristics of Phosphate-Solubilizing Bacteria Isolated from Acid Soil of Cikopomayak, West Java, Indonesia - HAPPY WIDIASTUTI (Microbiology Indonesia, 2008)
Phosphate-solubilizing bacteria were isolated from acid soil from Cikopomayak. Microbiological assay showed that the bacteria were Gram negative, rod-shaped, and lacked red pigment on Pikovskaya medium. Isolate A synthesized red pigment on nutrient agar medium, while isolate B formed slightly red pigment on nutrient agar medium as well as on Voges Proskauer medium. The ratio of clearing zone to colony for isolate A and B were approximately 2.1 and 1.9, respectively. Biochemical assays showed that both isolates A and B utilized glucose, lactose, sucrose, mannitol, glycerol, mannose, urea, indole, and produced catalase, but neither produced amylase and oxidase. The bacteria are identified as Serratia marcescens. The ability to solubilize phosphate decreased or was even lost when subcultured on nutrient agar medium. However, the ability to solubilize phosphate was recovered gradually with the addition of phosphate. The results presented here suggest that the ability to solubilize phosphate and to synthesize the red pigment may be inversely correlated.